Man as Subject of Education: Islamic and Western Philosophical Review of Freedom and Responsibility - Ahmad Mahfuzi; Muhamad Solehudin (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Freedom in the context of Islamic education is understood as the freedom to choose a way of life that aligns with religious teachings, while in Western philosophy, it is more focused on autonomy and critical thinking within a pluralistic society. This article explores the relationship between freedom and responsibility in education by comparing Islamic and Western perspectives through a qualitative literature review of both classical and contemporary works. The findings indicate that, despite differences in approach, both traditions agree that freedom must always be accompanied by responsibility to develop individuals who are not only intellectually capable but also contribute positively to society. An ideal education system should integrate these two values to shape well-rounded individuals—intellectually, morally, and socially—ensuring that education remains holistic and relevant in the era of globalization. This study provides deeper insights into how education can cultivate individuals who are not only intelligent but also responsible, both personally and socially, thereby contributing to the formulation of more relevant and applicable educational objectives in today’s interconnected world.